(untitled) (Nigerian Journal of Pharmaceutical Research, 2021)
Background: Terminalia macroptera Guill. &Perr. (combretaceae) is a flowering plant with several ethno-medicinal claims. However, the dearth of information on its analgesic property has necessitated this study. Objectives: to evaluate the anti-nociceptive potential of ethanol extract of Terminalia macroptera stem bark (TMSB) in mice. Materials and Methods: Male and female mice of weight range 22 – 25g were randomly allotted into seven groups (n= 5) and treated as follows: Group I received 0.5 mL distilled water orally (negative control), Groups II-V were orally administered ethanol extract of T. macroptera stem bark (TMSB) at 50, 100, 200, and 400 mg/kg respectively while groups VI-VII received piroxicam 10 mg/kg and pentazocine 2 mg/kg intraperitoneally respectively as standards. The same treatment pattern was adopted for both pain models: tail immersion and acetic acid-induced writhing assays. Data were expressed as mean ± standard error of mean (SEM) using two-way analysis of variance (ANOVA) followed by Tukey’s and Bonferroni’s multiple comparisons tests with p < 0.05 taken as significance. Results: The ethanolic extract of Terminalia macroptera stem bark showed significant dose-dependent anti-nociceptive activity at 100 and 400 mg/kg (2.95±0.41 and 2.9±0.31 respectively) 60 min post-treatment compared to the negative control group in the tail immersion test. Significant inhibition of nociception (0.20±0.20) was obtained at 400 mg/kg compared to the negative control group in the acetic acid-induced writhing test. Conclusions: The ethanol extract of Terminalia macroptera stem bark exhibited dose-dependent anti-nociceptive potential in both tail immersion and acetic acid-induced writhing assays in mice.